PENERBITAN SERTIPIKAT HAK MILIK YANG BERASAL DARI ALAS HAK SURAT PERNYATAAN YANG KEMUDIAN DINYATAKAN PALSU (STUDI KASUS MA NO. 1339/K/Pdt/2009) - DAHLIA ROSARI MELANI SIAHAAN (PREMISE LAW JURNAL, 2014)
ABSTRACT A certificate is strong evidence of the right which means that, as long as it cannot be proved either by physical or judicial data attached on it, it has to be accepted as valid data. In the ownership of a certain object, the person has to prove that it is his, as it is stipulated in Article 1865 of the Civil Code. The land rights, used as the issuance of the land ownership certificate in the Land Office, is a proof which can be used as a means of judicial evidence of ownership or the control of a piece of land, either in the written form or based on the witness’ statement. The objective of the research was to analyze the Ruling of the Supreme Court No. 1339/Pdt/2009 on the Issuance of Certificate which comes from a letter of notification which is later considered as forgery. The result of the research shows that the existence of an underhanded letter as the basis for the issuance of an Ownership Certificate is recognized in the Government Regulation No 24/1997 on Land Registration. Nevertheless, in order to be used as the right to issue the Ownership Certificate and to have legal force for evidence, the underhanded letter must meet the procedure and requirement stipulated in Article 24, Paragraph PP No 20/1997. Keywords: Issuance of Certificate, Ownership, Land Rights, False Letter of Notification